The Middle Kingdom under the Big Sky : A History of the Chinese Experience in Montana - Johnson, Mark T., 1974- (Book collections on Project MUSE., 2022)
"The Middle Kingdom under the Big Sky seeks to deepen understanding of the Chinese history of the region by recovering their stories in their own words and by understanding the Chinese experiences in Montana through a global lens"--